Grafica polígonos en el plano cartesiano e identifica sus lados y ángulos - Del Rio Roldan, Cesar Andres (2018)
The purpose of education is to train people capable of achieving their ethical, intellectual, artistic, cultural, physical, spiritual and religious fulfillment, promoting the formation and consolidation of their identity and self-esteem and their adequate and critical integration in society. The student interprets reality and makes decisions based on mathematical knowledge that contribute to their context. The student searches, systematizes and analyzes information to understand the world around him, solve problems and make decisions related to the environment. Flexible use of mathematical strategies and knowledge in various situations, from which she develops arguments and communicates her ideas through mathematical language, as well as various representations and resources. The didactic strategy is based on active methods where it indicates that learning in the individual proceeds from the general to the particular and from the indifferent to the precise. Therefore, to facilitate the learning of mathematics and, at the same time, the assessment and learning of the students will allow us to effectively see the expression skills of each student.